Polyaniline/Pure Carbon Assemblies as Efficient Self‐standing Metal‐free Oxygen Electrodes in Alkaline Media for Zn‐Air Batteries. Issue 10 (16th April 2020) - Zhang, You; Liu, Jie; Fang, Zhengsong; Lin, Xiaofeng; Zhang, Wenchao; Yu, Dingshan
Abstract: A facile design and fabrication of self‐standing metal‐free polyaniline (PANI)@carbon nanotubes (CNTs) composite membrane was initially proposed by straightforward noncovalent wrapping the polymer around pure CNTs. Without introduction of extra heteroatoms into CNTs, the optimized PANI@CNTs composite exhibits a much better electrocatalytic performance for oxygen evolution reaction (OER) than pure CNTs via favorable interfacial modification with PANI to largely expose the active sites of on the surface of pure CNTs. Besides, it displays good oxygen reduction reaction (ORR) performance. When directly utilized as bifunctional air electrode without extra additive agents, the composite membrane‐enabled rechargeable Zn‐air batteries not only deliver a high peak power density (201.9 W g −1 ) and a large energy density (850.3 Wh kgZn −1 ), but also present robust cycling performance for 216 cycles with a high energy efficiency of 57.8%. Abstract : An efficient self‐standing metal‐free polyaniline @carbon nanotubes (PANI@CNTs) membrane catalyst is designed and synthesized via a facile solution casting approach. Without introducing any heteroatoms into carbon lattices, the newly‐produced composite catalyst exhibits remarkably improved oxygen evolution activity relative to pure CNTs. Notably, it can be directly used as an additive‐free bifunctional oxygen electrode to endow a Zn‐air battery with good charge/discharge performance.